TEACHERS' RE-ORIENTATION: KEY TO REPOSITIONING NIGERIA'S EDUCATION SYSTEM FOR SUSTAINABLE DEVELOPMENT (Journal of Association of Educational Management and Policy Practitioners, 2026)
Re-orientation is the deliberate process of changing individual’s or group’s mindset, attitudes, values, knowledge, and behaviors to align with new realities, expectations, or developmental goals. Therefore, this paperexamined the critical role of teachers' re-orientation in repositioning Nigeria's education system to achieve sustainable development. It highlights how continuous professional development and re-training programs are essential in equipping teachers with relevant knowledge, pedagogical skills, and values needed for inclusive, equitable, and future-focused education. The transformative learning theory guided this paper. Itreviewed empirical literature and analyzes global best practices to establish the relevance of teacher re-orientation in improving instructional quality, aligning with curriculum reforms, and promoting sustainable development. Findings reveals that many Nigerian teachers lack sufficient awareness of sustainability concepts and digital competencies, indicating a pressing need for structured national re-orientation frameworks that would enhanced optimal teachers’ re-orientation. It therefore,concluded that the sustainable developmentof any nation in the 21st century lies in the hands of its teachers. Therefore, the paper suggested and recommended policy-driven strategies among others forthe implementation of effective teacher re-orientation programs that are not just necessary but critical to achieving the nation’s sustainable development.